PENGARUH PARTISIPASI ANGGARAN DAN JOB RELEVAN INFORMATION TERHADAP PENURUNAN INFORMASI ASIMETRI - Ernie Riswandari (Universitas Bunda Mulia, 2017)
Budgetting carries behavioral problem that can have important effect on the effectiveness of organization. This study to examine the influency of participatory budgeting and job relevant information toward descent of asimetric information.This research make use of deskriptif assosiatif method with utilized technic anlysis datas are linier regresion, F-test and T - test.Result shows participatory budgetting and job relevant information simultanously have significant toward descent of asymetric information and so does partially.If asimetric information go down, its will to descent of budgetary slack. Keywords : Participatory Budgeting, Job Relevant Information, Asimetric Information, Bundgetary Slack